Did Global Financial Crisis Impact the Islamic Banking Efficiencies? Evidence from Malaysian Islamic Banks - Abdus Samad (Global Review of Islamic Economics and Business, 2018)
First, this paper investigated the loan and deposit efficiencies of Malaysian Islamic banks during 2008-2013 applying the non-parametric technique, Data Envelopment Analysis (DEA), and found that the average technical efficiency (TE) of loan financing was 83%, 88%, 87%, 95%, 100%, and 94% and the average technical efficiency for deposit mobilizations was 87%, 94%, 94%, 96%, 92%, and 96%. Only four banks in 2008, two bank in 2009, three banks in 2010, two banks in 2011-2013 are both technically and scale efficient in loan production. On the other hand, only four banks in 2008 and 2009, five banks in 2010 and 2011, three banks in 2012, and five banks in 2013 are both technical and scale efficient in deposit mobilizations. Second, the paper compares the efficiencies of Islamic banks between the global financial crisis (GFC) and the post global financial crisis (PGFC) in determining whether the efficiencies of banks between the GFCP and PGFCP are stable. Both parametric and non-parametric tests found no significant difference in the efficiencies between the two periods suggesting that the efficiencies of the Malaysian Islamic banks were stable.